URGENSI SIDANG PRANIKAH SEBAGAI UPAYA PEMBENTUKAN PROFESIONALITAS ANGGOTA POLRI: STUDI KASUS DI POLRES SERAM BAGIAN BARAT - Narahaubun, Muhammad Ikhsan; Jamaa, La; Kabakoran, Abu Bakar (TAHKIM, 2023)
The purpose of this thesis research is to find out how the study according to the law regarding the Premarital Trial, then the premarital hearing procedure at the West Seram Police Station, and the relation between the Premarital Trial and the professionalism of the Police in building precision. The research methodology used is qualitative research. This research is also a type of field research with an analytical descriptive approach. This thesis succeeded in photographing the relationship between the marriage law and regulations within the police, namely regulation number 9 of 2010 which was later refined by regulation number 6 of 2018, that the prenuptial trial is not contradictory because in KUA there is also premarital coaching even though it has similarities but material reinforcement is different. Meanwhile, the pre-marriage trial procedure is in accordance with rule number 9 of 2010 which must be completed with requirements for every prospective bride of the police station. Departing from this process, the relationship between pre-marital hearings and professionalism can be achieved. Because the material of the premarital hearing in principle strengthens every member of the police is able to take full responsibility both for his institution and family.Keywords: Premarital Trial, household, professionalism.